EDUCATION OF QRIS USAGE AS A DIGITAL PAYMENT MODEL TO UMKM IN KELURAHAN MADE SURABAYA: EDUKASI PENGGUNAAN QRIS SEBAGAI MODEL PEMBAYARAN DIGITAL PADA UMKM DI KELURAHAN MADE SURABAYA - Falah, Fathi; Diyanah, Khuliyah Candraning; Pawitra, Aditya Sukma; Dhamayanti, Yeni; Saleh, Tania Ardiani; Jassey, Babucarr (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: The Quick Response Code Indonesian Standard (QRIS) is not yet widely embraced by small and medium enterprises (UMKM) in Kelurahan Made, Surabaya. Many business owners are unaware of QRIS’s benefits and methods of use, underscoring the need for effective education to facilitate their transition to a secure digital payment system. Objective: This initiative seeks to promote digital payment standardization among UMKM in Kelurahan Made by introducing QRIS and providing hands-on practice. Additionally, we assist UMKM with the QRIS registration process, empowering them to confidently adopt non-cash payment methods. Method: The program includes engaging socialization, informative counseling, and practical training involving six UMKM, along with personalized support for QRIS registration. Results: We are pleased to report an 85% attendance rate among our targeted participants, all of whom successfully began using QRIS in their transactions. Conclusion: Our educational and coordinated efforts in promoting QRIS have effectively enhanced financial literacy and improved transaction efficiency among UMKM. As QRIS adoption continues to grow, the digital transformation of the payment ecosystem in the kelurahan becomes increasingly attainable.